ED OUT (Education Source Trust) Business Planning Marketing Strategy with SWOT Analysis - Damar Nugroho; Nuria Safitri; Najma Khansa (Journal of Public Policy Analys, 2024)
The purpose of this study is to explore the role of SWOT analysis in managing a company's marketing strategy. In an ever-changing business context, SWOT analysis is key in the formulation and execution of marketing strategies that are adaptive to the dynamics of the business environment. This research adopts a qualitative descriptive approach with a focus on the management of ED OUT (Education Source Trust) as the subject of analysis. Through the use of questionnaires, data was obtained from 40 respondents to assess the strengths, weaknesses, opportunities and threats relating to marketing and sales strategies over a six-month period. Questionnaire results from 40 respondents, consisting of university students and students, revealed that ED OUT's main strengths lie in appropriate resource consulting services (70.0%), qualified human resources (40.0%), and resource persons with strong academic and practical expertise (77.5%). However, the price aspect of the service (40.0%) shows potential for improvement. The main weaknesses of ED OUT are lack of familiarity in the community (57.5%), limited market access (40.0%), and lack of a clear competitive advantage (17.5%), with an average weakness of 38.3%. Opportunities available to ED OUT include partnerships or acquisitions (35.0%), expansion of services (65.0%), market expansion (50.0%), and adoption of new technologies (32.5%), with an average opportunity of 45.6%. However, ED OUT is also faced with threats in the form of intense competition (42.5%), changing market trends (17.5%), and changing consumer preferences (27.5%), with an average threat of 29.1%.